On the drivers of inflation in different monetary regimes - Daniel G. Garcés Díaz (Banco de México, 2020)
This document proposes a general macroeconomic framework to analyze the behavior of inflation. This approach has two characteristics. The first is the distinction of monetary regimes based on the number of shocks that have a permanent effect on the price level. When all shocks have a permanent impact, the regime determines the inflation rate, as in inflation targeting. On the other hand, when there is only one shock with permanent effects, the regime determines the price level. An example of this is a regime with a fixed exchange rate. Even if there is no explicit target for the domestic price level, this becomes determined by the operation of a regime of this type. The second characteristic comes from the factors that Granger cause the rate of inflation or the price level. With this, a new perspective on four different historical cases emerges. One is the German hyperinflation; the second is that of the United States for a very long sample. For Brazil and Mexico, the analysis demonstrates that their inflationary processes' complexity arises from the regime changes they have gone through.
Keywords: C32; E41; E42; E52; 330; Pricing Equation; Money; Exchange Rate; Inflation Predictability